2021
DOI: 10.1002/ijgo.13745
|View full text |Cite
|
Sign up to set email alerts
|

The awareness levels of women for gynecologic cancer in Turkey: A cross‐sectional study

Abstract: Objective To investigate the awareness levels of women for gynecologic cancers and the affecting factors. Methods This descriptive and cross‐sectional study was conducted with 321 women. Data were collected using a Personal Information Form and the Gynecologic Cancer Awareness Scale (GCAS). Results The women's mean score (± standard deviation) on the GCAS was 151.08 ± 3.84. It was determined that the awareness of gynecologic cancer in the women who had undergone gynecologic examination and cervical smear test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The research ndings revealed that women who had previously undergone gynecological examinations had signi cantly higher levels of awareness. Similarly, other studies in the literature have reported that women who have undergone gynecological examinations are more conscious [25][26][27]. Awareness of cancer symptoms is an important determinant for early diagnosis and screening [28].…”
Section: Discussionmentioning
confidence: 88%
“…The research ndings revealed that women who had previously undergone gynecological examinations had signi cantly higher levels of awareness. Similarly, other studies in the literature have reported that women who have undergone gynecological examinations are more conscious [25][26][27]. Awareness of cancer symptoms is an important determinant for early diagnosis and screening [28].…”
Section: Discussionmentioning
confidence: 88%
“…Our participants who took pap smear tests were more aware of gynecologic cancers than those who did not. Also found that women who took pap smear tests were more aware of gynecologic cancers than those who did not (40).…”
Section: P a P E R A C C E P T E Dmentioning
confidence: 96%
“…Additionally, gaining awareness on the modifiable and unmodifiable factors that lead to cancer plays an important role in mobilizing the behavior of health seeking. 5 6 Awareness and health-seeking behaviors are associated with the self-care concept of individuals. The self-care of individuals involves activities that are started and performed by the individuals themselves to maintain their life, health, and state of wellbeing.…”
Section: Introductionmentioning
confidence: 99%